PENGKULTUSAN BAHASA ARAB SEBAGAI BAHASA AGAMA: PERSPEKTIF FILSAFATA DALAM PENGAJARAN DAN PEMBELAJARAN BAHASA ARAB DI INDONESIA - Faradisi, Roghibah Jadwa; Uyyun, Ajeng Nadlifah Qurrotul (Proceedings of International Conference on Islamic Civilization and Humanities, 2024)
The phenomenon of worshiping Arabic as an exclusive and normative religious language, as well as the shift towards desacralization as a means of communication, has had a significant influence on Arabic language teaching and learning patterns. The traditional approach which focuses on grammatical aspects stems from the historical aim of Muslims studying Arabic to understand religious teachings from the Koran, Sunnah and classical Arabic literature, by considering translation and analysis of i’rab. In contrast, modern educational patterns prioritize Arabic as a practical means of communication, reflecting the contemporary goal of interacting with Arabic-speaking communities globally, given its status as an official language in 22 countries and an international language recognized by the United Nations. This shift underscores the diversity of philosophical perspectives regarding the nature of language and its implications for educational practices in Arabic language learning.